Textbook language: Incentive or obstacle - Šefer Jasmina; Lazarević Emilija; Stevanović Jelena (Zbornik Instituta za pedagoška istraživanja, 2008)
The criticism of the current language in school textbooks indicates the gravity of this problem in our environment and the need to solve it. The first step in approaching this problem is studying the reception of primary school textbooks. In the first part of the paper we discuss all primary school textbooks from the fifth to the eighth grade with regard to the frequency of textbook usage and the perception of the difficulty of textbook language. In the second part of the paper there is an additional analysis of history, geography, biology, physics and chemistry textbooks from the fifth to the eighth grade with regard to the reasons for which pupils find them difficult. This preliminary research comprised in total 120 pupils from an urban school, thirty from each fifth to eighth grade. We analyzed the textbooks of the Institute for Textbook Publishing and Teaching Aids, which are used most frequently in our educational practice, and hence can represent the general situation of the problem. Bearing in mind the limited size of the sample of pupils, the results are used only as an illustration and should encourage new studies on a more extensive sample. Textbook language is often difficult since it is mostly insufficiently comprehensible, longwinded and with many data. In natural sciences, physics and chemistry, pupils give up studying from the textbook. The textbooks in narrative subjects lead the way with respect to their usage, among which everybody finds history textbooks most difficult. Geography and biology textbooks were evaluated differently, depending on the grade and success of the pupils declaring themselves. The results present a guideline to the current and new writers of our textbooks, critics and publishing houses.